Variabel-Variabel yang Mempengaruhi Struktur Keuangan Perusahaan Makanan dan Minuman Go Public di Bursa Efek Surabaya - Makhmud Zulkifli (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2008)
Thepurpose of this research is to study the effect of sales growth rate on asset structure, size of the company and the leverage of operating level in.financial structurefor thefirms that listing in Surabaya Stock Exchange. Judgment sampling and purposive sampling are used as a research methodology. Data is collected from 15 F dan B firms that have 5 year range (2000-2005). Furthermore, in order to measure the effect of independent variables simultaneousl y to.financial structure, F-test at significance (a) 5% is used. Conversely, dependent variables used t-test at the same level of significance .Finall y, the result of those tests are show that simultant effect does not impact to the.financial structure thus others tests are shows the other way around. Then it conclude that : sales growth rate, assets structure and degree of operating leverage do not have an impact significantl y to the.financial structure.